Juridical Basis of Murabahah Bil Wakalah Contracts at Islamic Banks - Astika Nurul Hidayah; Zeehan Fuad Attamimi; Safitri Mukaromah; Ira Hapsari (UM Purwokerto Press, 2023)
The wakalah agreement that appears in financing schemes in Islamic banks becomes a series with the murabahah agreement. This series of contracts then appears in financing in the form of a murabahah bil wakalah contract. The specific purpose of this research is to find out and analyze the juridical basis of the murabahah bil wakalah contract in positive law and Islamic Law in Indonesia. This research is categorized as legal research with a normative juridical method. The normative juridical approach used is the statute approach. The data collection method in this research uses cross methods, namely literature study, observation and interviews, according to the types and sources of data needed. Until now, there are no rules governing murabahah bil wakalah as a unit in Islamic bank financing products, both rules in positive law and Islamic law in Fatwa DSN MUI. Therefore, the juridical basis for murabahah bil wakalah financing comes from the juridical basis for each murabahah contract and wakalah contract, whether from the Law, Regulations of the Financial Services Authority of the Republic of Indonesia, or other laws and regulations, as well as Fatwa DSN MUI.